Manajemen Aset Sebagai Upaya Pelestarian Bangunan Bersejarah di Kota Bandung - Akbar, Roos; Wijaya, I Ketut (Journal of Regional and City Planning, 2008)
Historical buildings in the City of Bandung are facing several problems in their functionality changes, physical and the architecture/design changes, neglect, absence of local regulations on historic building conservation and lack of spatial information systems of assets. The city has tried to control through licensing, control over city planning, and assistance. However, the fact that problems still occur in the field showed the government’s efforts  are not yet effective. This paper aims to propose the use of management assets as a tool to conserve the historical building in Bandung. Employing the approach in assest management, all historical buildings in Braga area in City of Bandung are assessed and categorized. Using the ﬁve stages of asset management the result shows that managing and conserving historical building will be much more systematically easier. It is recommended that asset management as an approach need to be employed in the effort to preserve historical buildings.